2023
DOI: 10.1038/s41467-023-36728-1
|View full text |Cite
|
Sign up to set email alerts
|

Spintronic leaky-integrate-fire spiking neurons with self-reset and winner-takes-all for neuromorphic computing

Abstract: Neuromorphic computing using nonvolatile memories is expected to tackle the memory wall and energy efficiency bottleneck in the von Neumann system and to mitigate the stagnation of Moore’s law. However, an ideal artificial neuron possessing bio-inspired behaviors as exemplified by the requisite leaky-integrate-fire and self-reset (LIFT) functionalities within a single device is still lacking. Here, we report a new type of spiking neuron with LIFT characteristics by manipulating the magnetic domain wall motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…Figures 5(g) and (h) illustrate the LIF and LIFT characteristics, respectively. Using a synthetic antiferromagnetic heterostructure to control the magnetic domain wall motion by Joule heating, which enables the device to fire spikes with a high rate and low energy consumption [85]. These results show a novel way of implementing bio-inspired spiking neurons with spintronic devices that have advantages over traditional CMOS or emerging nonvolatile memory technologies.…”
Section: Artificial Neuronsmentioning
confidence: 91%
“…Figures 5(g) and (h) illustrate the LIF and LIFT characteristics, respectively. Using a synthetic antiferromagnetic heterostructure to control the magnetic domain wall motion by Joule heating, which enables the device to fire spikes with a high rate and low energy consumption [85]. These results show a novel way of implementing bio-inspired spiking neurons with spintronic devices that have advantages over traditional CMOS or emerging nonvolatile memory technologies.…”
Section: Artificial Neuronsmentioning
confidence: 91%
“…[183] Motion and switching of perpendicular magnetic anisotropy domains by spin-orbit torque and chiral coupling have also been demonstrated to enable "NOT", "NAND", and "NOR" gates (Figure 18b). [184] Based on SOT-driven magnetic domain wall motion in synthetic antiferromagnetic heterostructures, Wang et al [186] have recently demonstrated spintronic leaky-integrate-fire spiking neurons with self-reset and winner-takes-all for neuromorphic computing. These advances in prototype devices shall stimulate future efforts on developing more energy-efficient perpendicular SOT logic devices.…”
Section: Prototype Perpendicular Sot Logic Devicesmentioning
confidence: 99%
“…[ 184 ] Based on SOT‐driven magnetic domain wall motion in synthetic antiferromagnetic heterostructures, Wang et al. [ 186 ] have recently demonstrated spintronic leaky‐integrate‐fire spiking neurons with self‐reset and winner‐takes‐all for neuromorphic computing. These advances in prototype devices shall stimulate future efforts on developing more energy‐efficient perpendicular SOT logic devices.…”
Section: Prototype Perpendicular Sot Logic Devicesmentioning
confidence: 99%
“…Early works have shown the potential of binary states (P/AP) MTJs as artificial synapsesfunctional junctions between neuronsin emulating short-term plasticity and long-term potentiation for learning and cognition processes. , Furthermore, artificial synapses endowed with multistate (>2) digital or analog functionalities are posited to be more energy-efficient with enhanced learning accuracy and data acquaintance. Multistate or analog artificial synapse concepts built upon spatially varied arrangements of MTJs, e.g., in series, and domain wall racetracks, have been explored, albeit with weakly differentiated TMR (<5%) between states, unreliable read-write arising from their inherent thermal instability, and incompatibility with existing CMOS architectures. , On the other hand, the design of a compound synapse comprising a parallel array of MTJs on a shared SOT write channel has not been realized until date . Such a design potentially offers well-defined independent states and a reduced number of dedicated transistors for individual bit readout and write operations in the artificial neural network (ANN).…”
Section: Introductionmentioning
confidence: 99%